2013
DOI: 10.1002/jgrc.20177
|View full text |Cite
|
Sign up to set email alerts
|

Impact of bio‐optical data assimilation on short‐term coupled physical, bio‐optical model predictions

Abstract: [1] Data assimilation experiments with the coupled physical, bio-optical model of Monterey Bay are presented. The objective of this study is to investigate whether the assimilation of satellite-derived bio-optical properties can improve the model predictions (phytoplankton population, chlorophyll) in a coastal ocean on time scales of 1-5 days. The Monterey Bay model consists of a physical model based on the Navy Coastal Ocean Model and a biochemical model which includes three nutrients, two phytoplankton group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 59 publications
2
47
0
2
Order By: Relevance
“…Where CV is low, a negative correlation skill indicates poor performance in simulating weekly fluctuations, rather than seasonal cycles. Skilled simulation of short-term fluctuations is still a challenging task for complex marine ecosystem models (see, e.g., Allen et al, 2007;Stow et al, 2009;Shulman et al, 2013).…”
Section: Skill In Simulating the Satellite Data Evolution In Represenmentioning
confidence: 99%
See 1 more Smart Citation
“…Where CV is low, a negative correlation skill indicates poor performance in simulating weekly fluctuations, rather than seasonal cycles. Skilled simulation of short-term fluctuations is still a challenging task for complex marine ecosystem models (see, e.g., Allen et al, 2007;Stow et al, 2009;Shulman et al, 2013).…”
Section: Skill In Simulating the Satellite Data Evolution In Represenmentioning
confidence: 99%
“…However, the assimilation of satellite-derived optical data into ecosystem models is still in its infancy. Shulman et al (2013) demonstrated that the assimilation of phytoplankton absorption can improve the short-term predictions of chlorophyll and PFT ratios, in a five-day assimilative simulation in the Monterey Bay. However, to the authors' knowledge, the benefits of assimilating satellite-derived optical data for long-term biogeochemical simulations have yet to be tested.…”
Section: Introductionmentioning
confidence: 98%
“…Ciavatta et al, 2014) or phytoplankton absorption (e.g. Shulman et al, 2013). For complex coastal regions that are dominated by case 2 waters, an explicit spectrally resolved in-water optics model opens the possibility of directly assimilating RSRs and avoids the costly requirement of calibrating an empirical IOP algorithm that is regionally specific.…”
Section: Multiband Assimilationmentioning
confidence: 99%
“…There are now examples of operational and pre-operational global systems that routinely assimilate Chl a products (Ford et al, 2012). Additionally, there has been further experimentation with assimilating alternative remotely sensed apparent optical properties (AOPs) such as the vertical attenuation coefficient at 443 nm, Kd 443 (Ciavatta et al, 2014) and inherent optical properties (IOPs) such as phytoplankton absorption (a ph ), as described in Shulman et al (2013). A map of the Great Barrier Reef region, with the colour bar denoting the water depth, markers denoting the population centres (red triangles), IMOS NRS sites (yellow triangles), GBRMPA MMP Water Quality Meters (WQMs; yellow circles) and points of interest referred to in the text (red circles), with the glider track (white line adjacent to Lizard Island).…”
Section: Introductionmentioning
confidence: 99%
“…The extent of the domain was chosen to correspond to the location of the 2010 BIOSPACE field experiment [Shulman et al, 2013]. It is likely that the spatial and temporal scales in this domain are correlated.…”
Section: Implementation For Mapping Of Algal Blooms In Monterey Baymentioning
confidence: 99%